2018
DOI: 10.1111/tra.12571
|View full text |Cite
|
Sign up to set email alerts
|

RNA localization regulates diverse and dynamic cellular processes

Abstract: At the nexus of specialized cellular responses are localized enrichments of protein activity. The localization of messenger RNA (mRNA) coupled with translational control often plays a crucial role in the generation of protein concentrations at defined subcellular domains. Although mRNA localization is classically associated with large specialized cells, such as neurons and embryos, RNA localization is a highly conserved paradigm of post-transcriptional regulation observed in diverse cellular contexts. Function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 55 publications
0
63
0
Order By: Relevance
“…Neurons are highly polarized, with long distances between the soma, where RNAs are synthesized in the nucleus, and projections (axons/dendrites/neurites), where cells must quickly respond to stimuli (Figure 1A). These cell types have therefore been a critical model system to understand how RNA localization controls gene expression using imaging‐based approaches as reviewed previously 1–5 . Several neurological diseases, including amyotrophic lateral sclerosis (ALS) and fragile X syndrome (FXS), have been associated with misregulated RNA localization in neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Neurons are highly polarized, with long distances between the soma, where RNAs are synthesized in the nucleus, and projections (axons/dendrites/neurites), where cells must quickly respond to stimuli (Figure 1A). These cell types have therefore been a critical model system to understand how RNA localization controls gene expression using imaging‐based approaches as reviewed previously 1–5 . Several neurological diseases, including amyotrophic lateral sclerosis (ALS) and fragile X syndrome (FXS), have been associated with misregulated RNA localization in neurons.…”
Section: Introductionmentioning
confidence: 99%
“…RNA subcellular localization is critical to a myriad of cellular processes (Buxbaum et al, 2015;Chin and Lécuyer, 2017;Ryder and Lerit, 2018). Researchers have also discovered that RNA localization plays a significant role in RNA viruses (Chou et al, 2013), with functions ranging from regulating sites of virion assembly (Becker and Sherer, 2017) to disrupting host mitochondrial function (Somasundaran et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that mRNA localization is a prevalent, potent, and conserved mechanism used by cells to regulate protein sorting (Lecuyer et al, 2007;Mili et al, 2008;Cajigas et al, 2012;Ryder et al, 2018). Although there are several pathways by which mRNAs are localized, active motor-based transport along cytoskeletal filaments is a commonly used mechanism.…”
Section: Introductionmentioning
confidence: 99%